In vitroscreening and evaluation of antivenom phytochemicals from Azima tetracanthaLam. leaves against Bungarus caeruleusand Vipera russelli - Janardhan,Bhavya (2014)
Background : Snakebites are considered a neglected tropical disease that affects thousands of people worldwide. Although antivenom is the only treatment available, it is associated with several side effects. As an alternative, plants have been extensively studied in order to obtain an alternative treatment. In folk medicine, Azima tetracanthaLam. is usually used to treat snakebites. The present study aims to provide a scientific explanation for the use of this plant against snakebite. The extracts of shade dried leaves of A. tetracanthawere tested for in vitroinhibitory activity on toxic venom enzymes like phosphomonoesterase, phosphodiesterase, acetylcholinesterase, hyaluronidase etc. from Bungarus caeruleusandVipera russellivenoms.Results : The ethylacetate extract rendered a significant inhibitory effect on the phosphomonoesterase, phosphodiesterase, phospholipase A2 and acetylcholinesterase enzymes.Conclusions : The present study suggests that ethylacetate extract of A. tetracanthaleaves possesses compounds that inhibit the activity of toxic enzymes from Bungarus caeruleusandVipera russellivenom. Further pharmacological andin vivostudies would provide evidence that this substance may lead to a potential treatment against these venoms.